Stability of novel urinary biomarkers used for lupus nephritis - Cody, Ellen M.; Rose, James E.; Huang, Bin; Qiu, Tingting; Brunner, Hermine I.; Devarajan, Prasad (Frontiers in Pediatrics, 2022)
Background: The Renal Activity Index for Lupus (RAIL), is a composite score of six urinary biomarkers (neutrophil gelatinase–associated lipocalin (NGAL), monocyte chemoattractant protein-1 (MCP-1), kidney injury molecule-1 (KIM-1), ceruloplasmin, adiponectin, and hemopexin) used to monitor lupus nephritis activity in children. We tested stability of RAIL biomarkers prior to meaningful clinical use. Methods: Urine samples were tested by ELISA under shipping conditions, freeze/thaw, ambient and longer-term storage. Statistical analysis was performed via Deming Regression, Bland-Altman and Spearman Correlation Coefficient. Results: Biomarker concentration were comparable to freshly collected urine following storage at -80C for up to 3 months, and at 4 or 25C up to 48 hours followed by -80C. Neither shipping on dry or wet ice exposure nor addition of two freeze-thaw cycles led to loss of signal, with excellent Spearman Correlation coefficients under all conditions. Conclusions: RAIL biomarkers are stable following short-term storage at clinically relevant conditions.